Transpapillary Gallbladder Stents Can Stabilize or Improve Decompensated Cirrhosis in Patients Awaiting Liver Transplantation. Issue 9 (October 2015) - Tujios, Shannan R.; Rahnama-Moghadam, Sahand; Elmunzer, Joseph B.; Kwon, Richard; Singal, Amit G.; Anderson, Michelle A.; Wamsteker, Erik-Jan; Taylor, Jason R.; Scheiman, James; Elta, Grace; Fontana, Robert J.; Piraka, Cyrus R.
<x xml:space="preserve">Abstract</x> Goals: To describe the short-term and long-term outcomes in 34 consecutive decompensated cirrhotic patients with symptomatic gallbladder disease undergoing transpapillary gallbladder stent (TGS) placement. Background: Endoscopic TGS placement is a minimally invasive means of treating symptomatic gallbladder disease in poor surgical candidates. Study: Between June 2005 and June 2011, 34 patients with cirrhosis and symptomatic gallbladder disease underwent attempted TGS placement. Results: Median patient age was 52 years, 56% were hospitalized, and 48% were listed for liver transplantation. The median model for end-stage liver disease (MELD) score was 15 (range, 6 to 40) and 88% were Child-Turcotte-Pugh class B/C. A double pigtailed stent was successfully placed in 94% of the patients. At 1-month follow-up, clinical improvement was noted in 82% of the treated subjects and the MELD scores in 14 of 22 (64%) evaluable subjects improved or stabilized. Actuarial transplant-free survival was 53% in the liver transplant candidates with a mean follow-up of 352 days, whereas survival was 44% in the 18 nontransplant candidates with a mean follow-up of 1.5 years. Periprocedural complications included pancreatitis in 5 patients, cholangitis in 3, and 1 patient with cystic duct perforation. In addition, 2 subjects had symptomatic bleeding from traumatic duodenal ulcerations 2 years after TGS placement that necessitated stent removal. Conclusions: Endoscopic TGS placement was technically feasible in 94% of decompensated cirrhotics and was associated with a relatively low rate of periprocedural (26%) and long-term complications (6%). Stabilization or improvement in clinical status and MELD scores was seen in the majority of treated patients.